Gaya Bahasa dan Fungsi Iklan pada Majalah LifeWear Uniqlo : Language Style and Function of Advertisements in Uniqlo's LifeWear Magazine - Sultan Maulana Malik Zidan; Umul Khasanah (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
Abstract. The purpose of this study was to analyze the linguistic styles found in the three clothing categories of LifeWear Magazine Uniqlo Edition 08 Spring & Summer 2023: 'wardrobe essentials', 'art of everyday life' and 'Melbourne magic'. . This is a method of descriptive analysis using reading and note-taking methods for the language style data published in LifeWear Magazine Uniqlo Edition 08 Spring & Summer 2023